MUSINT Le Collezioni archeologiche egee e cipriote in Toscana Ricerche ed esperienze di museologia interattiva - Jasink, Anna Margherita; Tucci, Grazia; Bombardieri, Luca (Strumenti per la didattica e la ricerca, 2011)
MUSINT is an interactive museological network devoted to the Tuscan archaeological collections which enables the creation of an innovative display itinerary through the collections of Aegean and Cypriot antiquities, so that exhibits originating from different museum institutions can be appreciated. This has led to the creation of a "museum of museums" which responds to the need to offer a display system that can be "visited" by a broad and variegated public. The arrangement of the book itself reflects the true nature of the MUSINT project and its character as a research worksite, enhanced by past experience, and a bridge for the appreciation of new perspectives within a scientific, technological and cultural universe that is open and in continual movement.